2014
DOI: 10.5860/crl.75.5.684
|View full text |Cite
|
Sign up to set email alerts
|

Don’t Fear the Reader: Librarian versus Interlibrary Loan Patron-Driven Acquisition of Print Books at an Academic Library by Relative Collecting Level and by Library of Congress Classes and Subclasses

Abstract: Recently, a great deal of literature on patron-driven acquisition (PDA) has been published that addresses the implementation and results of PDA programs at academic libraries. However, despite widespread worries that PDA will lead to unbalanced collections, little attention has been paid to whether patrons' and librarians' purchasing differ significantly. This study analyzes librarians' and PDA patrons' acquisitions at an academic library by relative collecting level and by subject (that is, Library of Congres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…They also found that there were differences between how patrons and librarians spent acquisitions dollars, but again, those differences were minor. 20 In 2015, two studies were conducted at the University of Florida and Iowa State University comparing DDA/PDA and librarian selection. At the University of Florida, librarian-selected e-books were less expensive on average ($88.45) than PDA titles ($123.04), but librarian-selected e-books had a higher average cost per use ($22.21) than PDA titles ($8.88).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also found that there were differences between how patrons and librarians spent acquisitions dollars, but again, those differences were minor. 20 In 2015, two studies were conducted at the University of Florida and Iowa State University comparing DDA/PDA and librarian selection. At the University of Florida, librarian-selected e-books were less expensive on average ($88.45) than PDA titles ($123.04), but librarian-selected e-books had a higher average cost per use ($22.21) than PDA titles ($8.88).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Patron-driven acquisition (PDA) has become widespread after its very positive reception and it is "estimated that there are around 400-600 institutions worldwide with active PDA programs" (Esposito et al, 2012) quoted in (Tyler et al, 2014). The latter article is exceptionally well researched with 60 references, many of which further containing over a dozen references.…”
Section: Patron-driven Acquisition or Demand-driven Acquisitionmentioning
confidence: 99%